Social studies and the press : keeping the beast at bay? - Crocco, Margaret Smith (Emerald Publishing Limited : IAP- Information Age Publishing Inc, 2005)
In this collection of 19 articles contributors cover the nature of the relationship between the press and social science, especially in education.
Keywords: Social sciences -- Study and teaching.; Journalism.; Education -- Teaching -- Subjects -- Social Science.; Teaching of a specific subject.; Educational: Social sciences, social studies.; elektronické knihy; electronic books